Leveraging food system transformation in Latin America through scaling high impact business models - Simon, Nataniel; Wadt, Lucas; Prudenciano, Lucas; Newman, Richard; Zulu-Hume, Mercy F.; Sharma, Ashish; Martínez Barón, Deissy; Costa, Ciniro (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Key messages: 1) A framework was developed and applied to identify Climate-Smart Food Systems (CSFS) business models in the Latin America (LATAM) region with the potential to implement and scale climate mitigation and resilient practices across several food production systems. 2) Through the analysis, a pipeline of eight high-impact potential companies were identified to facilitate matchmaking with private sector investors. 3) Selected CSFS companies include agroforestry (i.e., coffee and cocoa), regenerative livestock production and silvipastoral systems, with positive impacts on social (e.g., gender and youth) and economic aspects. 4) Some of the most important challenges identified for implementing and scaling CSFS include: 1) access to capital, especially for long-term projects; 2) access to information and technical assistance; and 3) market validation for some products, especially fruits. 5) Regarding technical assistance, focus should be on implementing measurement, reporting and verification (MRV) of emissions, accessing carbon markets and providing guidance for adoption of CSFS practices and project review and discussion for up- and middle-stream companies. 5) The CIAT-CCAFS Impact Assessment Tool showed potential for evaluating CSFS performance of companies (i) potential impact assessment and (ii) additionality of investments regarding mitigation, adaptation and productivity.